DESAIN PEMBELAJARAN KONTEKS SOSIAL-SOSIETAL DALAM PRAGMATIK DENGAN METODE KOOPERATIF TEKNIK INVESTIGASI - Kunjana Rahardi (STKIP Siliwangi, 2020)
Abstract Pragmatic learning must be research based. By basing on research, pragmatic learning in language majors and language education will be of high quality. Until now, pragmatic learning is still based on the views of Western experts. On the basis of that concern, the authors sought to examine specific culture-based pragmatics related to the socio-societal context. The results of the study are utilized in pragmatic learning. The main objective of this study is to describe the design of social-societal context learning models in pragmatics. The paradigm that was followed was the Ignasian-based reflective learning paradigm. The learning method applied is the cooperative learning method. The technique applied is a group investigation technique. Furthermore, this research is useful in the following matters: (a) improving and improving the quality of pragmatic learning in tertiary institutions; (b) produce researchers in the field of reliable pragmatics because they are used to wrestling with pragmatic research; (c) developing pragmatics, especially pragmatics based on specific culture.Keywords: Group investigation technique; cooperative learning method; reflective teaching Pembelajaran pragmatik harus berbasis riset. Dengan mendasarkan pada riset, pembelajaran pragmatik di jurusan-jurusan bahasa dan pendidikan bahasa akan berkualitas. Hingga sekarang, pembelajaran pragmatik masih didasarkan pada pandangan pakar Barat. Atas dasar keprihatinan itu, penulis berusaha meneliti pragmatik berbasis kultur spesifik terkait konteks sosial-sosietal. Hasil kajian tersebut dimanfaatkan dalam pembelajaran pragmatik. Tujuan utama penelitian ini adalah menggambarkan desain model pembelajaran konteks sosial-sosietal dalam pragmatik. Paradigma yang diikuti adalah paradigma pembelajaran reflektif berbasis Ignasian. Metode pembelajaran yang diterapkan adalah metode pembelajaran kooperatif. Adapun teknik yang diterapkan adalah teknik investigasi kelompok (grup-investigation technique). Selanjutnya, penelitian ini bermanfaat dalam hal-hal berikut: (a) memperbaiki dan meningkatkan kualitas pembelajaran pragmatik di perguruan tinggi; (b) menghasilkan periset-periset bidang pragmatik yang andal karena mereka sudah terbiasa bergulat dengan riset pragmatik; (c) mengembangkan ilmu pragmatik khususnya pragmatik yang berbasis kultur spesifik. Kata Kunci: Group investigation technique; cooperative learning method; pembelajaran reflektif